Social democracy and labour market policy : developments in Britain and Germany - Roder, Knut, 1965- (Routledge research in comparative politics, 2003)
This topical study reflects on problems faced by social democratic parties in government when espousing policies of severe pragmatism and fiscal prudence, and provides a perspective to both parties' changes in labour market policies.